Comparative evaluation of cerium oxide nanoparticles and calcium hydroxide as intracanal medicament against Enterococcus faecalis on tooth substrate: An in vitro study - Dona Sanju; Veronica Aruna Kumari; Toby Thomas; Julie Toby Thomas; Ramakrishna Sujeer (Wolters Kluwer Medknow Publications, 2022)
Aim: The aim of this study is to compare the antibacterial efficacy of cerium oxide nanoparticles and calcium hydroxide as intracanal medicaments against Enterococcus faecalis on tooth substrate - an in vitro study. Materials and Methods: The experiment was conducted in three stages. In Stage 1, antibacterial susceptibility test of three test materials, cerium oxide nanoparticles, calcium hydroxide, and vancomycin against E. faecalis was done using disc diffusion method. In Stage 2, determination of minimal inhibitory concentration and minimum bactericidal concentration of the cerium oxide nanoparticles was done by tube dilution method. In Stage 3, determination of CFU was carried out using dentinal blocks at 1-day and 5-day intervals at two different dentinal depths (200 μm and 400 μm) for calcium hydroxide (Group 1), cerium oxide nanoparticle dispersion (Group 2), a mixture of calcium hydroxide and cerium oxide nanoparticles (Group 3), and sterile water (Group 4). Results: The reduction of E. faecalis achieved by cerium oxide nanoparticles dispersion on day 5 was 66.9% as against 46.7% as shown by mixture of the two medicaments and 34.8% by calcium hydroxide paste alone on day 5 at 400-μm depth. Conclusion: Cerium oxide nanoparticles show a significantly higher antibacterial efficacy when compared to calcium hydroxide and its combination.